Strong electro-optic absorption spanning nearly two octaves in an all-fiber graphene device - Park, Nam Hun; Ha, Seongju; Chae, Kwanbyung; Park, Ji Yong; Yeom, Dong Il (Nanophotonics, 2020)
An efficient electro-optic transition control is reported in all-fiber graphene devices over a broad spectral range from visible to near-infrared. The ion liquid-based gating device fabricated onto a side-polished fiber with high numerical aperture significantly enhances the light-matter interaction with graphene, resulting in strong and nonresonant electro-optic absorption of up to 25.5 dB in the wavelength ranging from 532 to 1950 nm. A comprehensive analysis of the optical and electrical properties of the device fabricated with monolayer and bilayer graphene revealed that the number of graphene layers significantly impacts on the performance of the device, including modulation depth and driving voltage. Wavelength-dependent optical response is also measured, which clearly characterizes the electronic bandgap dispersion of graphene. The device exhibited more efficient electro-optic modulation in the longer wavelength region, where the maximum light modulation efficiency of 286.3%/V is achieved at a wavelength of 1950 nm.
Keywords: Comprehensive analysis; Electro-optic modulation; Electronic band gaps; High numerical apertures; Light-matter interactions; Modulation efficiency; Optical and electrical properties; Side-polished fiber; electro-optic absorption; fiber optic devices; graphene